KARAKTERISTIK ALTERASI DAN TEKSTUR URAT KUARSA PADA PIT BARANI, CEBAKAN EMAS MARTABE, KABUPATEN TAPANULI SELATAN, PROVINSI SUMATRA UTARA: ALTERATION AND QUARTZ-VEIN TEXTURES CHARACTERISTIC AT BARANI PIT OF MARTABE GOLD DEPOSITS, SOUTH TAPANULI REGENCY, NORTH SUMATRA PROVINCE - Nada Salsabila Deva; Yuningsih, Euis Tintin; Fachrudin, Kurnia Arfiansyah; Saala, Nur Afrianti; Triyunita, Ade (Pusat Sumber Daya Mineral Batubara dan Panas Bumi, 2020)
Barani Pit is part of the PT Agincourt Resources Contract of Work, located in Aek Pining Village, Batangtoru District, South Tapanuli Regency, North Sumatra. The Barani Pit is an open pit mine, with epithermal deposit type in the form of veins which host for more concentration of metal elements. This study aims to find out the alteration characteristics and texture variations of quartz veins that are abundant in the Barani Pit area and to identify the texture of quartz veins carrying economic mineralization. The pit mapping method is used to get samples, and alteration mineral identification using analytical spectral devices (ASD), as well as geochemical analysis to determine grade content of Au, Ag, and Cu elements. The results showed that the developing alteration zone consisted of argillic (kaolinite+illite+ smectite), advanced argillic (quartz+kaolinite+dickite), and silicification (quartz+chalcedony+ kaolinite). Quartz textures of the veins that developed in the study area consisted of massive quartz, crustiform, crustiform-colloform, brecciated, bladed, and saccharoidal. The texture of mineralization bearing veins with high grade gold content were crustiform-colloform, banded, followed by massive quartz oxide, and lattice bladed. These veins are associated with kaolinite + dickite clay minerals, moderate to high oxidation states, and are associated with grey sulphides containing high grade up to Au 76.65 ppm and Ag 34 ppm.